Study on the effectivenss of nebulized fentanyl citrate as modality of analgesia in children with acute pain - Yahaya, Raden Nezarul Raden (2018)
Introduction: To assess the effectiveness of nebulized fentanyl citrate in treating children presenting with acute severe pain of various aetiologies. Methods: Patients aged 5 to 15 years old presented with acute severe pain of any causes were enrolled into the study through convenient sampling and received intravenous preparation of fentanyl citrate at dose of 4 mcg/kg administered through oxygen driven nebulizer circuit. Pain scores were assessed at pre-treatment and subsequently at 5 minutes interval until 60 minutes post-treatment using Wong and Baker faces pain scale. Vital signs and potential adverse events were also monitored. Results: 42 children with acute pain of various causes participated in this study and tolerated the nebulized fentanyl citrate well. 2 patients were withdrawn due to insufficient pain control post treatment. The pain aetiologies were categorized into fractures (n=14), soft tissue injuries (n=15) and abdominal pain (n=11). The mean pain score at 10 minutes on nebulized fentanyl administration decreased by 2.65 (95% CI 2.62 to 2.73) from the baseline. Pain score continued to decrease at 15 minutes (mean pain score difference 4.20; 95% CI 4.01 to 4.39) followed by a sustained plateau pain score at 20 minutes until 60 minutes. The pain score reduction at alltime intervals measured post-treatment were highly significant (P <0.001). No adverse events or vital signs deterioration observed following nebulized fentanyl. Conclusion: Nebulized fentanyl citrate at dose of 4 mcg/kg given through oxygen drive nebulizer circuit was effective in treating children with acute severe pain without causing adverse events and should be considered as a modality of acute pain treatment in children population.